NORMS FOR STIFFNESS COEFFICIENTS OF SOME MAIN TYPES OF GLUED CORNER JOINTS OF STRUCTURAL ELEMENTS OF ONE-LAYER PINE WOOD BOARDS - Marinova, Assia (Innovation in Woodworking Industry and Engineering design, 2012)
Presently, there is an increase in manufacture of case furniture made of one-layer solid wood boards. The strength and stiffness of the corner joints between the furniture’s structural elements are of great importance for the strength, shape stability and durability of this kind of furniture in the service conditions of its long term usage. In this study the data are given about the experimentally established stiffness coefficients of some of the most frequently used glued corner joints of structural elements made of one-layer solid pine wood boards under compression bending test. On this basis norms for stiff-ness coefficients are propounded. It was established that the type of the joints has a significant influence on their stiffness under bending loading. The determined stiffness coefficients and their normative values of the tested glued corner joints of one-layer solid wood boards of Scots pine under bending loading can be used by furniture designers in strength and deformation investigations of solid wood furniture with the help of computer programs based on the Finite element method, as well as for the quality assurance control in manufacturing.